ANALISIS TEGANGAN SETIAP BUS PADA SISTEM TENAGA LISTRIK GORONTALO MELALUI SIMULASI ALIRAN DAYA - Harun, Ervan Hasan (Jurnal Sainstek, 2012)
This study aims to analyze the voltage of each bus on Electric Power System Gorontalo under normal conditions. The problem of this study is limited to the determination of the voltage at various points / bus and channels. The approachmethod of power flow used in this study is the Newton-Rhapson by an accuracyfactor of 0.0001 through simulations with the aid of ETAP 4.0 (Electrical Transient Analyzer Program).